2010
DOI: 10.1007/s00167-010-1130-4
|View full text |Cite
|
Sign up to set email alerts
|

No difference in early functional outcomes for mini-midvastus and limited medial parapatellar approaches in navigation-assisted total knee arthroplasty: a prospective randomized clinical trial

Abstract: Patients desire less pain and faster recovery of range of knee motion after total knee arthroplasty (TKA). While minimal invasive surgery (MIS) TKA appears to meet these needs, concerns exist regarding component malpositioning. Navigation systems can reduce the incidence of component misalignment. The present prospective randomized study compared limited medial parapatellar (LMPP) and mini-midvastus (MMV) approaches in 30 patients who had bilateral simultaneous primary TKAs. Each patient underwent LMPP on one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…However an RCT comparing MIS to standard approach in obese patients did show earlier improvement in clinical outcomes and no compromise of component position in the MIS group [45]. At a time when concerns regarding surgical training are prescient, the MMV approach may have advantage due to the ease with which it may be adopted by surgeons familiar with the standard MPP approach and indeed can be extended into a standard approach if needed [46]. It is increasingly recognised that there is a significant learning curve for certain minimally invasive approaches [8] and that this may be of relevance to the low volume surgeon [23].…”
Section: Discussionmentioning
confidence: 90%
“…However an RCT comparing MIS to standard approach in obese patients did show earlier improvement in clinical outcomes and no compromise of component position in the MIS group [45]. At a time when concerns regarding surgical training are prescient, the MMV approach may have advantage due to the ease with which it may be adopted by surgeons familiar with the standard MPP approach and indeed can be extended into a standard approach if needed [46]. It is increasingly recognised that there is a significant learning curve for certain minimally invasive approaches [8] and that this may be of relevance to the low volume surgeon [23].…”
Section: Discussionmentioning
confidence: 90%
“…Five studies were included for meta-analysis of VAS [12], [22][24], [27]. Subgroup analyses suggested that the mini-midvastus approach significantly decreased VAS at postoperative 2 weeks ( p <0.01), and no differences were seen between the two groups at the time points of 3 day ( p  = 0.42), 6 week ( p  = 0.22), 3 month ( p  = 0.82), 6 month ( p  = 0.80).…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference in length of stay or analgesia intake was observed when comparing these different muscular approaches [19]. Many of these studies were focusing on the mini-midvastus approach [3,10,16,21]. Maybe this transmuscular approach is not so innocent as sometimes inferior quadriceps function [29], or higher muscle enzymes were observed in mini-midvastus and mini-subvastus approaches through stretching or cutting of the muscle [22,29].…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, the minimally invasive medial parapatellar approach may be the easiest approach to convert from the classic approach [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation